PENGELOLAAN ASET TETAP BARANG MILIK NEGARA DITINJAU DARI PERMENKES NO 9 TAHUN 2018 TENTANG PEDOMAN PENGELOLAAN BARANG MILIK NEGARA DI LINGKUNGAN KEMENTERIAN KESEHATAN Penelitian pada Balai Teknik Kesehatan Lingkungan dan Pengendalian Penyakit Kelas II Amb - Zadrak Romeo Kermite; Septo Pawelas Arso; Nurhasmadiar Nandini (Jurnal Kesehatan Masyarakat (Undip), 2021)
Abstract : This study aims to analyze the management of fixed assets of State Property (BMN) at BTKLPP Class II Ambon with reference to the Minister of Health Regulation Number 9 of 2018 concerning Guidelines for BMN Management in the Ministry of Health. The research was focused on the aspects of determining the usage status of BMN and the elimination of BMN. The study uses a qualitative method with an analytic descriptive approach. The results showed that the determination of the usage status of BMN at BTKLPP Ambon has not been going well. This evidenced by the findings that most of the fixed assets of BMN have not been assigned their usage status. The process of eliminating BMN's fixed assets also did not go well. One of the reasons is that the usage status has not been determined. The process of managing assets remains interrelated and when one aspect is neglected, it will affect other aspects. Keywords : Fixed Assets, State Property, Regulation